Anatomical and Histochemical Studies of Prenatal Prostate Gland in Buck (Capra hircus) - Farooqui, M.M. (Indian Journal of Veterinary Anatomy, 2019)
A study was conducted on development of prostate gland of 70 goat foeti, divided into five groups viz.Group I (0-30 days), Group II (31-60 days), Group III (61-90 days), Group IV (91-120 days) and Group V (121-till term). The primordium of the prostate gland was appeared on 56th day of gestation as an aggregation of solid cells just beneath the transitional epithelium of urethra. Solid tubules got canalized on 66th day of gestation. Up to 3rd month of gestation, the pars disseminata was confined to dorso-lateral aspect of the urethra. The collagenous fibres appeared on 98th day onwards. The ducts were separated by venous spaces. The endothelial lining of the venous spaces revealed intense PAS, acid and alkaline phosphatase reactions. The glandular tissue was distributed all around the urethral lumen after 108 day of gestation. Canalization of the secretory end pieces began on 118th day onwards. The epithelial cells of the collecting tubules showed moderate to intense PAS, mild to glycogen, moderate and mild to alkaline and acid phosphatase, respectively, in all groups. Lipid granules were observed in the cytoplasm of epithelial cells.